Modeling of the co-transport of cryoprotective agents in a porous medium as a model tissue. - Xu, X; Cui, Z (2003)
Cryopreservation is likely the choice for long-term preservation of natural and engineered tissues, and high concentration multiple cryoprotective agents (CPAs) are usually used in such a process. To achieve high cell viability after cryopreservation, cells at all locations within the tissue must be protected properly by the CPAs during freezing. It is hence essential to know the distribution and concentration of CPAs within the tissue during multiple-CPA addition, to maximize cell survival and minimize tissue damage. In this work, a model to describe the CPA transport during multiple-CPA addition in a one-dimensional porous medium, as a simplified model of living tissue, was developed on the basis of the Maxwell-Stefan (M-S) equations. The UNIFAC and UNIQUAC models were used to evaluate the activity coefficients, and the Siddiqi-Lucas correlation was used for estimation of Maxwell-Stefan diffusivities. Simulations were carried out to examine the effect of temperature, tissue property, CPA type and the interactions between solutes on the CPA transport within construct during the CPA addition. It was found that these parameters, especially the interactions between the different CPA molecules, which was neglected before, significantly affect the transport of each individual CPA component. It is hence concluded that the traditional single-component analysis on the CPA diffusion is not adequate to quantify the multiple-CPA distribution in the tissue, particularly when the CPA concentrations are relatively high.